Portable audiometric screening platforms used in low-resource settings: a review. Issue 2 (5th November 2018) - Jayawardena, A; Waller, B; Edwards, B; Larsen-Reindorf, R; Esinam Anomah, J; Frimpong, B; Gina, A; Netterville, J; Saunders, J; Basura, G J
Abstract: Background: Millions of people across the world suffer from disabling hearing loss. Appropriate interventions lead to improved speech and language skills, educational advancement, and improved social integration. A major limitation to improving care is identifying those with disabling hearing loss in low-resource countries. Objectives: This review article summarises information on currently available hearing screening platforms and technology available from published reports and the authors' personal experiences of hearing loss identification in low-resource areas of the world. The paper reviews the scope and capabilities of portable hearing screening platforms, including the pros and cons of each technology and how they have been utilised in low-resource environments. Conclusion: Portable hearing screening tools are readily available to assess hearing loss in low-resource areas. Each technology has advantages and limitations that should be considered when identifying the optimal methods to assess needs in each country.